2008
DOI: 10.1080/01421590701753575
|View full text |Cite
|
Sign up to set email alerts
|

Addressing current problems in teaching pathology to medical students: blended learning

Abstract: Background: Forces influencing the remodelling of medical curricula have clouded the visibility of pathology teaching yet its mastery is central to the study of medicine. The shortage in the workforce available for routine clinical diagnosis, research and teaching, and increasing student numbers have driven the development of innovative teaching methods. Aims: To develop teaching methods which improved student satisfaction and engagement in their learning of pathology, and which also accommodated larger classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…The inclusion of thoughtfully designed course components that encourage active participation in the learning process are critical to the success of blended courses. [10][11][12] Blended course design models are effective in teaching pharmacy students in the areas of microbiology, adult acute care medicine, pharmaceutical biotechnology, and cardiovascular pharmacotherapy. [13][14][15][16] In general, these courses were well received by students and instructors reported that the blended, or hybrid, approach was an effective way for students to achieve course objectives.…”
mentioning
confidence: 99%
“…The inclusion of thoughtfully designed course components that encourage active participation in the learning process are critical to the success of blended courses. [10][11][12] Blended course design models are effective in teaching pharmacy students in the areas of microbiology, adult acute care medicine, pharmaceutical biotechnology, and cardiovascular pharmacotherapy. [13][14][15][16] In general, these courses were well received by students and instructors reported that the blended, or hybrid, approach was an effective way for students to achieve course objectives.…”
mentioning
confidence: 99%
“…14 Interactive lectures takes active involvement of the student with the subject matter to develop understanding that is mostly not achieved in the lecture halls. 15 Several studies have shown that students consider video based demonstrations as an effective learning tool.…”
Section: Discussionmentioning
confidence: 99%
“…Ainda que 16 professores, dos quais 13 médicos patologistas, e haja certa autonomia com relação aos conteúdos a serem abordados, urge definir um core curriculum em Patologia Básica e de Sistemas e qual abordagem didática e pedagógica renderá maior retenção de conteúdo e aprendizado. Experiências como as relatadas por Maley et al 21 mostram que a autonomia, parte das estratégias de estudo autodirigido (SDL), é fundamental ao processo de aprendizado. Contudo, os alunos reconhecem e valorizam claramente a presença de professores comprometidos com a transmissão de conhecimentos, formação e motivação de novos profissionais.…”
Section: Experiência Na Universidade Federal Do Paranáunclassified